Digitalisasi Data Potensi Sumber Daya Alam Desa Teluk Lada Berbasis Geographic Information System (GIS) - Hidayat, Amat; helmi, Muhammad; Seprianti, Restu (Universitas Pahlawan Tuanku Tambusai, 2026)
Teluk Lada Village, located in the coastal area of Pandeglang Regency, boasts diverse natural resource potential, including fisheries, agriculture, and marine tourism. However, data on this potential has not been systematically documented, complicating development planning and sustainable resource management. This study aims to describe the process of digitizing village natural resource potential data using a Geographic Information System (GIS) to support integrated regional management and development. The method used was participatory mapping, involving the village government, local communities, and a team of students. The activity stages included field data collection, location coordinates acquisition using GPS devices, spatial data processing with QGIS software, and data validation with village stakeholders. The results of this activity produced a digital map of agricultural, fisheries, and tourism potential that can be accessed interactively. This digitization has been proven to simplify the planning process, increase data transparency, and open up investment opportunities based on local potential. Thus, the application of GIS is an innovative solution for realizing effective, accurate, and sustainable village natural resource management.